Ratio of Confidence and Adaptability of Chinese Students - A V Sheptura; A I Krupnov (Peoples' Friendship University of Russia (RUDN University), 2014)
The article analyses the peculiarities of confidence and adaptability of Chinese students studying in the Russian University, and its ratio in the factorial structure.